PENGEMBANGAN MODUL METODE PROYEK UNTUK MENGETAHUI KETERAMPILAN PROSES SAINS (KPS) SISWA PADA LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - irma zarwinda zarwinda (Lantanida Journal, 2019)
This study was conducted to develop a project method module on the subject of  electrolyte  and non – electrolyte solution, to  assess the quality of the module based on the  experts suggestions, to get  the teacher and student responses to the  project method module, and know the KPS based student learning styles and the role project method module. The study was conducted in three schools in Banda Aceh (SMA Negeri 11, SMA Negeri 10 Fajar Harapan, and SMA Negeri 5 Banda Aceh) by  using quantitative research with research methods of  and development (R and D). The design of this study is Pre-test and Post-test Group. Experts assessment for the quality of module shows a score of 4.21 (good), the results showed that 90.67% teachers and 80.68% students responded positively to the module. Hypothesis testing is done toward  the pretest and posttest data based on students  from three schools with a significant level of 0.05%. The result from pretest data using Mann-Whiteney (U test) have a few different although it did not differ significantly. The result from posttest data using the t test  are not significantly. The role of the modul was based on the seen  average value of students KPS posttest  in three schools which is 72.19 with the criteria of "good" when using project method of chemitry module.